Biohacking and Longevity: Lifestyle Trends to Extend Life and Optimal Health - Mustar, Mustar (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the impact of biohacking practices on quality of life and healthy life expectancy (longevity) among individuals who adopt such lifestyles. Biohacking, which involves changes in diet, exercise, stress management, and the use of health-monitoring technology, has rapidly developed as an alternative lifestyle focused on health and longevity. A quantitative research method was employed by distributing questionnaires to 120 respondents actively engaged in biohacking practices. The results showed that most respondents experienced improvements in sleep quality, physical fitness, and mental well-being. Additionally, biohacking practices were found to have a positive correlation with perceptions of longevity, although challenges such as time constraints and financial costs remain obstacles. These findings provide insights into the potential of biohacking in promoting optimal health and extended lifespan, as well as the need to improve health and technological literacy to reach a broader population.